Endogenous tariffs and economic transformation: The case of Russian trade policies - Rolf J. Langhammer (Intereconomics, 1995)
There is a widespread consensus that trade policy reforms in the successor states of the former Soviet Union in general and in Russia in particular are subject to major obstacles which are larger than in Central and Eastern European transformation countries. The following paper discusses some crossroad decisions facing the implementation of Russian trade policies and analyses the major external constraints facing the Russian economy in this regard.
Keywords: 330; Außenwirtschaftspolitik; Zollpolitik; Systemtransformation; Russland